Hydrogel band-aid for bone repair as well as preparation method and application of hydrogel band-aid

Through a simple and controllable preparation method of hydrogel bandage, a hydrogel bandage loaded with a variety of metal ions is formed by combining polyethylene glycol succinimide succinate with alendronic acid, polyphenols and metal ions. The problems of low bioavailability and insufficient immunomodulation of osteoporosis fracture treatment in the prior art were solved, and high biocompatibility and multifunctional bone regeneration effect were achieved.

CN119258268AActive Publication Date: 2025-01-07SHANDONG UNIV

Patent Information

Application Number
CN202411795109.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-01-07
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Existing treatments for osteoporosis fractures have low bioavailability and insufficient regulation of bone immune system, which cannot effectively promote bone regeneration, and is difficult to meet complex biological needs in severe or challenging cases.

Method used

Using a simple and controllable hydrogel bandage preparation method, by mixing polyethylene glycol succinimide succinate with alendronic acid, polyphenol and metal ions, a hydrogel loaded with multiple metal ions is formed. Band-Aids use hydrogen bonds and metal coordination bonds to improve bone regeneration and angiogenesis capabilities and regulate the immune microenvironment.

Benefits of technology

Achieve high biocompatibility, stretchability and versatile hydrogel bandages, which can significantly enhance osteoblast activity, inhibit osteoclast function, promote angiogenesis and immune regulation, and are suitable for osteoporotic bone defects treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258268A_ABST
    Figure CN119258268A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of bone repair hydrogel, and discloses a hydrogel band-aid for bone repair and a preparation method and application thereof, and the preparation method comprises the following steps: mixing a polyethylene glycol succinimide succinate solution with an alendronate solution, dialyzing, and freeze-drying to obtain alendronate modified polyethylene glycol succinimide succinate; and uniformly mixing alendronate modified polyethylene glycol succinimide succinate, polyphenol, metal ions and water in proportion, carrying out solid-liquid separation, and drying the solid to obtain the hydrogel. The preparation process provided by the invention has the advantages of simplicity, convenience and rapidness, not only simplifies the production process, but also enhances the bone regeneration, angiogenesis and immunoregulation capabilities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bone repair hydrogels, and in particular relates to a hydrogel band-aid for bone repair and a preparation method and application thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Osteoporosis is a common degenerative bone disease that is challenging to repair due to decreased bone density and impaired microarchitecture, increased bone fragility and fracture susceptibility, especially in the elderly and postmenopausal women. Current treatments for osteoporotic fractures, such as bisphosphonates, are hampered by low bioavailability and insufficient bone immune regulation, making recovery from osteoporotic fractures challenging. To address these challenges, innovative materials are urgently needed that can not only support bone regeneration but also modulate the immune environment to promote healing.

[0004] Polyethylene glycol hydrogel bandages are innovative materials designed to cover bone defects, provide physical support, and promote bone tissue regeneration. These polyethylene glycol hydrogel bandages are highly tunable and reproducible, suitable for cross-linking and coupling with biomolecules (such as extracellular matrix mimetic peptides that promote cell adhesion and enzymatic degradation), and are considered by the FDA to be a generally recognized safe additive. However, the ability of polyethylene glycol hydrogel bandages to promote bone growth and repair defects is often limited and cannot meet the complex biological needs of bone regeneration, especially in severe or challenging cases. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a hydrogel bandage for bone repair and a preparation method and application thereof. The present invention provides a simple and controllable strategy for designing and manufacturing a hydrogel bandage with bone repair ability. Compared with the traditional solution casting-evaporation method, the reported assembly strategy has the advantages of simple and rapid process, which not only simplifies the production process, but also enhances the ability of bone regeneration, angiogenesis and immunoregulation.

[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions: In a first aspect, the present invention provides a method for preparing a hydrogel bandage for bone repair, comprising the following steps: The polyethylene glycol succinimidyl succinate solution and the alendronic acid solution are mixed, dialyzed, and freeze-dried to obtain alendronic acid-modified polyethylene glycol succinimidyl succinate; Alendronate-modified polyethylene glycol succinimidyl succinate, polyphenols, metal ions and water are mixed evenly in proportion, solid-liquid separation is performed, and the solid obtained by the solid-liquid separation is spread into a uniform thin layer, and after drying, a hydrogel band-aid is obtained.

[0007] The function of polyethylene glycol succinimidyl succinate is to form a complex by utilizing the hydrogen bonding between polyethylene glycol and polyphenols; the succinimidyl succinate at the end of polyethylene glycol interacts with alendronic acid, and alendronic acid is grafted onto the end of polyethylene glycol for loading and sustained release of alendronic acid. Polyethylene glycol is the main component of the entire hydrogel bandage.

[0008] The role of alendronic acid is currently a clinical drug for the treatment of osteoporosis, and alendronic acid is used to inhibit osteoclast activity; The functions of polyphenols are: hydrogen bond interaction with polyethylene glycol; forming a metal polyphenol network with metal ions; polyphenols also have the function of regulating the immune microenvironment.

[0009] Metal loading: Alendronate can form metal coordination bonds with metal ions; polyphenols can form metal polyphenol networks with metals. Using these two interactions, metal ions can be effectively loaded into hydrogel bandages.

[0010] Different types of metal ions have significant biological effects when properly dosed and released in a controlled manner, and therefore are valuable in bone repair materials. The addition of various metal ions (such as magnesium, calcium, strontium, zinc, copper, and iron) at optimal doses can significantly enhance the activity of osteoblasts, inhibit the function of osteoclasts, and promote angiogenesis. Therefore, the preparation of polyethylene glycol hydrogel bandages loaded with multiple metals is of great significance for the treatment of osteoporotic bone defects.

[0011] In some embodiments, the polyethylene glycol succinimidyl succinate is selected from one or a combination of methoxy polyethylene glycol succinimidyl succinate, two-arm polyethylene glycol succinimidyl succinate, four-arm polyethylene glycol succinimidyl succinate, or eight-arm polyethylene glycol succinimidyl succinate.

[0012] Preferably, the polyethylene glycol succinimidyl succinate is eight-arm polyethylene glycol succinimidyl succinate.

[0013] In some embodiments, the molar ratio of polyethylene glycol succinimidyl succinate to alendronic acid is 1:1-5, preferably 1:2.

[0014] In some embodiments, after mixing polyphenols with metal ions, metal ion-polyphenol complex nanoparticles are formed; The metal ion-polyphenol complex nanoparticle dispersion and the alendronic acid-modified polyethylene glycol succinimidyl succinate solution are then mixed evenly, the solid and liquid are separated, and the solid is dried to obtain the hydrogel.

[0015] Preferably, the molar ratio of metal ions, polyphenols and alendronic acid-modified polyethylene glycol succinimidyl succinate is 1.5-2.5:1:2-3, preferably 2:1:2.5.

[0016] In some embodiments, the polyphenol is selected from one or a combination of tannic acid, gallic acid, epigallocatechin gallate, catechin or anthocyanin.

[0017] Preferably, the polyphenol is epigallocatechin gallate.

[0018] In some embodiments, the metal ion is selected from one or a combination of calcium ion, zinc ion, magnesium ion or strontium ion.

[0019] Preferably, the metal ions are calcium ions and / or zinc ions.

[0020] In a second aspect, the present invention provides a hydrogel band-aid for bone repair, which is prepared by the preparation method.

[0021] In a third aspect, the present invention provides use of the hydrogel bandage for bone repair in treating osteoporotic bone defects.

[0022] The beneficial effects achieved by one or more embodiments of the present invention are as follows: (1) The preparation method of the present invention is simple and easy to implement. The present invention utilizes the coordination effect between metal and polyphenol and the coordination effect between metal and alendronic acid to obtain a flexible multifunctional metal-polyethylene glycol hydrogel band-aid. The present invention provides a universal method for rapidly preparing a hydrogel band-aid loaded with multiple metal ions and having excellent performance; (2) The hydrogel bandage obtained by the preparation method of the present invention has excellent stretchability (150%) and can achieve sustained release of various metal ions; (3) The hydrogel bandage obtained by the preparation method of the present invention has high biocompatibility (95%) for mouse mononuclear macrophages and mouse bone marrow mesenchymal stem cells, and has high osteogenic performance, osteoclast inhibition and immune microenvironment regulation capabilities, and can be used as a therapeutic bandage to accelerate the repair of bone defects. The present invention provides a simple and controllable strategy for the engineering design of multifunctional bone repair hydrogel bandages loaded with multiple metals, and has broad application prospects in the fields of osteoporotic bone defects and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0024] Figure 1 The present invention is a flow chart of the preparation method of the hydrogel band-aid for bone repair and the application of the hydrogel band-aid in Example 1; Figure 2 The macroscopic photographs of the preparation process of the hydrogel band-aid for bone repair in the embodiment of the present invention, wherein a is PZnE hydrogel; b is PCaE hydrogel; c is PZnCaE hydrogel; Figure 3 These are SEM images of the bone repair hydrogel band-aids containing different metal ions of the present invention, wherein a is PZnE hydrogel; b is PCaE hydrogel; c is PZnCaE hydrogel; Figure 4 The tensile mechanical property curves and tensile mechanical property statistical diagrams of the hydrogel band-aids with different metal ions of the present invention, wherein a is the tensile property curve; b is the tensile strength quantitative diagram; c is the fracture toughness quantitative diagram; Figure 5 The metal ion release curves of the hydrogel band-aid of different metal ions of the present invention, wherein a is the zinc ion release curve; b is the calcium ion release curve; Figure 6 is the biocompatibility of the hydrogel band-aid with different metal ions of the present invention, wherein a is the survival rate of RAW 264.7 cells; b is the survival rate of BMMSC cells; c is the survival rate of HUVEC cells; Figure 7 The osteogenic properties of the hydrogel band-aids with different metal ions of the present invention, wherein a is the osteogenic ability of different types of multi-metal bone repair hydrogels detected by real-time fluorescence quantitative PCR technology; b is the test result of the alkaline phosphatase (ALP) activity assay kit, and c is the test result of the alizarin red (ARS) activity assay kit; Figure 8 The osteoclastogenic performance of the hydrogel band-aid with different metal ions of the present invention, wherein a is a graph for detecting the activity of tartaric acid-resistant acid phosphatase; b is a quantitative graph for detecting the activity of tartaric acid-resistant acid phosphatase; Fig. 9 The angiogenesis performance of hydrogel band-aids with different metal ions of the present invention, wherein a is a graph of cell migration ability of hydrogel band-aids with different metal ions, and the scales of each graph in a are the same; b is a graph of angiogenesis of hydrogel band-aids with different metal ions, and the scales of each graph in b are the same; Fig.10The immunomodulatory performance of the hydrogel band-aid with different metal ions of the present invention, wherein a is a flow cytometric graph; b is the quantitative data of M1 type cells; c is the quantitative data of M2 type cells; Fig.11 The therapeutic effect of the hydrogel band-aid for bone repair in Example 1 of the present invention on osteoporotic bone defects in mice, wherein a is a control group; b is a hydrogel band-aid group containing calcium ions; c is a hydrogel band-aid group containing zinc ions; d is a hydrogel band-aid group containing calcium ions and zinc ions; Fig.12 This is a schematic diagram of the principle of using a hydrogel band-aid in an embodiment of the present invention to treat osteoporotic bone defects in mice. DETAILED DESCRIPTION

[0025] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0026] The present invention will be further described below in conjunction with the embodiments.

[0027] Example 1 A method for preparing a hydrogel band-aid for bone repair comprises the following steps: (1) Accurately weigh 1.6 g of sodium hydroxide in 20 mL of ultrapure water, and ultrasonicate at 25°C for 3 min to obtain a dissolved sodium hydroxide solution. Accurately weigh 2 g of alendronic acid in 10 mL of PBS, and add sodium hydroxide solution to adjust the solution pH to 7.4 to obtain a dissolved alendronic acid solution; Accurately weigh 1 g of eight-arm polyethylene glycol succinimidyl succinate in 10 mL of PBS and ultrasonicate at 25°C for 5 min to obtain a dissolved eight-arm polyethylene glycol succinimidyl succinate solution; The eight-arm polyethylene glycol succinimidyl succinate solution was mixed with the alendronic acid solution, stirred at 25° C. for 4 h, dialyzed for 48 h, and then freeze-dried to obtain alendronic acid-modified polyethylene glycol.

[0028] (2) Accurately weigh 30 mg of epigallocatechin gallate into 10 mL of PBS and dissolve it by ultrasonication at 25°C for 5 min to obtain a dissolved epigallocatechin gallate solution with a concentration of 3 mg / mL.

[0029] Accurately weigh 50 mg of zinc nitrate hexahydrate into 10 mL of ultrapure water and ultrasonicate at 25°C for 3 min to obtain a zinc nitrate hexahydrate solution with a zinc nitrate concentration of 5 mg / mL.

[0030] EGCG-Zn nanoparticles were obtained by mixing 1 mL of epigallocatechin gallate solution with 1 mL of zinc nitrate hexahydrate solution.

[0031] (3) Accurately weigh 250 mg of alendronic acid-modified polyethylene glycol in 10 mL of PBS and dissolve it by ultrasonication at 25°C for 3 min to obtain a dissolved alendronic acid-modified polyethylene glycol solution with a concentration of 25 mg / mL. Mix 0.5 mL of alendronic acid-modified polyethylene glycol solution with 1 mL of EGCG-Zn nanoparticles, centrifuge at 500 rcf for 3 min, remove the supernatant and collect the precipitate.

[0032] (4) Spread the precipitate evenly in a glass dish with a diameter of 2 cm to form a uniform thin layer. After drying, a self-supporting hydrogel bandage can be obtained. Figure 1 and Figure 2 As shown in a.

[0033] Example 2 A method for preparing a hydrogel bandage for bone repair, which differs from Example 1 in that the concentration of alendronic acid-modified polyethylene glycol is changed from 25 mg / mL to 50 mg / mL.

[0034] Example 3 A method for preparing a hydrogel bandage for bone repair, which differs from Example 1 in that the concentration of epigallocatechin gallate is changed from 3 mg / mL to 5 mg / mL.

[0035] Example 4 A method for preparing a hydrogel band-aid for bone repair, which differs from Example 1 in that the concentration of zinc nitrate hexahydrate is changed from 5 mg / mL to 10 mg / mL.

[0036] Example 5 A method for preparing a hydrogel band-aid for bone repair, which differs from Example 1 in that the centrifugal speed is changed from 500 rcf to 3000 rcf.

[0037] Example 6 A method for preparing a hydrogel band-aid for bone repair, which differs from Example 1 in that the centrifugation time is changed from 3 min to 10 min.

[0038] Example 7 A method for preparing a hydrogel bandage for bone repair, which is different from Example 1 in that the metal ion is changed from zinc nitrate hexahydrate to anhydrous calcium chloride with a concentration of 5 mg / mL. Figure 2 Middle b.

[0039] Example 8 A method for preparing a hydrogel bandage for bone repair, which is different from Example 1 in that the metal ion is changed from zinc nitrate hexahydrate to a mixed solution of anhydrous calcium chloride and zinc nitrate hexahydrate, the concentration of zinc nitrate hexahydrate is 2.5 mg / mL, and the concentration of anhydrous calcium chloride is 2.5 mg / mL. The prepared hydrogel is shown in Figure 2 Middle c.

[0040] Experimental Example 1: Performance testing of hydrogel bandages loaded with metal and with controllable release (1) SEM test The morphology of the hydrogel band-aids for bone repair prepared in Example 1, Example 7 and Example 8 was characterized. Figure 3 As can be seen from a, b and c, the thickness of the hydrogel band-aid is uniform on the micron scale and has a dense microstructure.

[0041] (2) Mechanical properties test The mechanical properties of the hydrogel band-aid for bone repair obtained in the example were quantitatively tested for tensile properties. Figure 4 As shown in a, b and c, PZnE is the hydrogel band-aid prepared in Example 1, and the hydrogel band-aid contains zinc ions; PCaE is the hydrogel band-aid prepared in Example 7, and the hydrogel band-aid contains calcium ions; PZnCaE is the hydrogel band-aid prepared in Example 8, and the hydrogel band-aid contains calcium ions and zinc ions.

[0042] When the hydrogel bandage contains calcium ions and zinc ions, the tensile strength of the PZnCaE hydrogel bandage reaches its maximum, reaching 530 kPa.

[0043] (3) Metal ion sustained release test 5 mg of the PZnCaE hydrogel bandage prepared in Example 8 was placed in a centrifuge tube containing 10 mL of PBS buffer solution (10 mM, pH 6.5). 0.1 mL of dialysate was taken out every day on the 0th, 2nd, 4th, 6th, 8th, 10th, 15th, 20th and 25th days of immersion, and then 0.1 mL of new buffer solution was added. After the sampling was completed, the released zinc ions and calcium ions were quantitatively analyzed using ICP-MS to draw a metal ion release curve. The metal ion release curve is shown in Figure 5 As shown, Figure 5 Figure a is the zinc ion release curve, and figure b is the calcium ion release curve. Under physiological pH conditions, the PZnCaE hydrogel bandage can continuously and stably release metal ions for about 30 days, which is very beneficial for bone repair and regeneration applications.

[0044] (4) Biocompatibility testing The biocompatibility of the metal-polyethylene glycol hydrogel bandage to mouse mononuclear macrophages (RAW 264.7) and mouse bone marrow mesenchymal stem cells (BMMSCs) was characterized by a cell proliferation and toxicity detection kit (CCK-8, purchased from Bio-Tech Co., Ltd.).

[0045] A 96-well cell culture plate was selected, and 5000 cells were inoculated in each well. After culturing overnight, the PZnE hydrogel band-aid prepared in Example 1, the PCaE hydrogel band-aid prepared in Example 7, and the PZnCaE hydrogel band-aid prepared in Example 8 were respectively immersed in the cell culture medium, and the concentration of the hydrogel band-aid was 5 mg / mL. After soaking for 24 hours, the supernatant was taken out, which was the hydrogel band-aid extract. 100 μL of the three types of hydrogel band-aid extracts were added to the cells respectively and cultured for 72 h. After the culture was completed, 10 μL of CCK-8 solution was added to each well. After 4 h of action, the absorbance was detected using an enzyme reader with an excitation wavelength of 480 nm. The biocompatibility curve is shown in the figure. Figure 6 As shown, a is the survival rate of RAW 264.7 cells; b is the survival rate of BMMSC cells; c is the survival rate of HUVEC cells; it can be seen that the polyethylene glycol hydrogel band-aids with different metal ions can maintain cell growth very well, and the cell survival rate can reach more than 95%.

[0046] (5) Osteogenesis performance test In order to study the potential application of the band-aid as bone repair, the osteogenic properties of the PZnE hydrogel band-aid obtained in Example 1, the PCaE hydrogel band-aid obtained in Example 7, and the PZnCaE hydrogel band-aid obtained in Example 8 were characterized. Figure 7 .

[0047] The PZnE hydrogel band-aid prepared in Example 1, the PCaE hydrogel band-aid prepared in Example 7, and the PZnCaE hydrogel band-aid prepared in Example 8 were respectively immersed in the cell culture medium, and the concentration of the hydrogel band-aid was 5 mg / mL. After soaking for 24 hours, the supernatant was taken out, which was the hydrogel band-aid extract. A 24-well cell culture plate was selected, and 50,000 mouse bone marrow mesenchymal stem cells (BMMSCs) were inoculated in each well. After culturing overnight, 500 μL of three types of hydrogel band-aid extracts were added to the cells and continued to be cultured for 10 days. After the culture was completed, the protein level in the cells was detected by real-time fluorescence quantitative PCR technology. The alkaline phosphatase (ALP, purchased from Beijing Solebow Technology Co., Ltd.) activity assay kit and the alizarin red (ARS, purchased from Beijing Solebow Technology Co., Ltd.) activity assay kit were used to detect the effects of different hydrogel extracts on the osteogenic ability of cells.

[0048] like Figure 7 As shown in Figure a, on the 10th day of osteogenic induction, the expression of osteogenic-related proteins such as human type I collagen, osteopontin, core binding factor, and bone morphogenetic protein 2 in BMMSCs in the calcium ion group increased significantly. Figure 7 As shown in b and c, alkaline phosphatase staining on day 14 and Alizarin Red S staining on day 21 of culturing BMMSCs showed that alkaline phosphatase activity and calcium deposition in BMMSCs cultured with PCaE and PZnCaE groups were significantly increased. Compared with the PZnE and control groups, the PCaE and PZnCaE groups slowly released Ca ions during the degradation process, promoting osteogenic differentiation through the phosphatidylinositol 3-kinase (PI3K) signaling pathway.

[0049] (6) Osteotomy performance test In order to study the potential application of the band-aid as bone repair, the osteoblastic performance of the PZnE hydrogel band-aid obtained in Example 1, the PCaE hydrogel band-aid obtained in Example 7, and the PZnCaE hydrogel band-aid obtained in Example 8 was characterized ( Figure 8 ).

[0050] The PZnE hydrogel band-aid prepared in Example 1, the PCaE hydrogel band-aid prepared in Example 7, and the PZnCaE hydrogel band-aid prepared in Example 8 were respectively immersed in cell culture medium, and the concentration of the hydrogel band-aid was 5 mg / mL. After immersion for 24 hours, the supernatant was taken out, which was the hydrogel band-aid extract. A 24-well cell culture plate was selected, and 50,000 mouse bone marrow mesenchymal stem cells (BMMSCs) were inoculated in each well. After culturing overnight, 500 μL of three types of hydrogel band-aid extracts were added to the cells and cultured for 7 days. After the culture was completed, the tartrate-resistant acid phosphatase (TRAP, purchased from Beijing Solebow Technology Co., Ltd.) activity assay kit was used to detect the effects of different hydrogel extracts on the osteoclastogenic ability of cells. The results showed that on the 7th day of inducing osteoclasts, except for the control group, the TRAP staining results of other experimental groups did not show obvious osteoclast formation (such as Figure 8 Quantitative analysis further confirmed that with the slow release of ALN, the osteoclast differentiation in the PZnE, PCaE, and PZnCaE groups was significantly inhibited (as shown in Figure 2a). Figure 8 (b). Therefore, the bone repair hydrogel bandage can achieve balanced regulation of osteoblasts and osteoclasts.

[0051] (7) Angiogenesis performance test Hydrogel bandages can promote angiogenesis and induce cell migration. Cell migration experiments were performed using human umbilical vein endothelial cells (HUVECs) on the PZnE hydrogel bandage obtained in Example 1, the PCaE hydrogel bandage obtained in Example 7, and the PZnCaE hydrogel bandage obtained in Example 8 to evaluate the migration ability of different metal hydrogel bandages on HUVECs.

[0052] The PZnE hydrogel band-aid prepared in Example 1, the PCaE hydrogel band-aid prepared in Example 7, and the PZnCaE hydrogel band-aid prepared in Example 8 were respectively immersed in cell culture medium, and the concentration of the hydrogel band-aid was 5 mg / mL. After soaking for 24 hours, the supernatant was taken out, which was the hydrogel band-aid extract. A 12-well cell culture plate was selected, and 100,000 HUVECs were inoculated in each well. After culturing overnight, a sterile 200 μL gun tip was used to scratch the well plate vertically, and then washed three times with PBS to ensure that there were no floating cells in the scratched area. 1 mL of the three types of hydrogel band-aid extracts were respectively added to the cells and cultured for another 24 days. After the culture was completed, the cell migration results were observed using an inverted fluorescence microscope. The results are as shown in Fig. 9 As shown in (a), the migration ability of the PZnCaE group was the strongest compared with the control group, PZnE group and PCaE group.

[0053] Subsequently, angiogenesis experiments were performed on the surface of matrix gel to evaluate the effects of different metal hydrogel bandages on angiogenesis. A 48-well cell culture plate was selected, and 200 μL of matrix gel was inoculated in each well and cultured at 37ºC for 30 minutes. Then, 100,000 HUVECs were inoculated in each well and cultured for 4 hours. After the culture, the results of cell angiogenesis were observed using an inverted fluorescence microscope. The PZnCaE group had significantly increased connection points and tube length, and had the strongest in vitro tube formation ability (e.g. Fig. 9 (b). Therefore, the hydrogel bandage can promote cell migration, improve angiogenesis, and promote fracture healing.

[0054] (8) Immune regulation performance test Regulating the polarization state of macrophages and inducing their transformation from M1 phenotype to M2 phenotype is crucial for promoting angiogenesis and bone repair. The hydrogel band-aids obtained in Example 1, Example 8 and Example 9 can effectively regulate the immune microenvironment and promote macrophage polarization. Flow cytometry was used to detect surface markers of macrophage polarization, such as Fig.10 As shown in (a). The proportion of M1 macrophages in the PZnE, PCaE, and PZnCaE groups was significantly reduced. Fig.10 As shown in middle b, the proportion of M2 macrophages increased significantly. Fig.10As shown in middle c, this indicates that the EGCG-containing hydrogel bandage can effectively regulate the transition of macrophages from M1 phenotype to M2 phenotype, which can provide a more favorable immune microenvironment and thus help enhance bone repair at the fracture site in patients with osteoporosis.

[0055] (9) Treatment of osteoporotic bone defects in rats using a hydrogel bandage for bone repair In order to further demonstrate the bone defect treatment potential of the hydrogel bandages obtained in Examples 1, 8 and 9, the effect of the hydrogel bandages in treating skull defects in osteoporotic rats was also studied.

[0056] Different types of hydrogel bandages were implanted into circular defects with a diameter of 8 mm on the skull of rats, such as Fig.12 The results of micro-computed tomography (micro-CT) are shown in Fig.11 As shown in Figure 2, the defect in the control group was obvious at the fourth week after surgery, with only a small amount of new bone formed near the fracture end. Fig.11 Compared with other groups, the PZnE group and PCaE group showed a trend of bone repair. Fig.11 As shown in Figures b and c, the defect area in the PZnCaE group was the smallest. At 8 weeks after surgery, the defect areas in all groups except the control group were reduced. Compared with the other groups, the bone repair effect in the PZnCaE group was better, as shown in Figure 2. Fig.11 As shown in middle d.

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrogel band-aid for bone repair, characterized in that: The steps include: The polyethylene glycol succinimidyl succinate solution and the alendronic acid solution are mixed, dialyzed, and freeze-dried to obtain alendronic acid-modified polyethylene glycol succinimidyl succinate; Alendronate-modified polyethylene glycol succinimidyl succinate, polyphenols, metal ions and water are mixed evenly in proportion, solid-liquid separation is performed, and the solid obtained by the solid-liquid separation is spread into a uniform thin layer, and after drying, a hydrogel band-aid is obtained.

2. The method for preparing a hydrogel band-aid for bone repair according to claim 1, characterized in that: The polyethylene glycol succinimidyl succinate is selected from one of methoxy polyethylene glycol succinimidyl succinate, two-arm polyethylene glycol succinimidyl succinate, four-arm polyethylene glycol succinimidyl succinate or eight-arm polyethylene glycol succinimidyl succinate or a combination thereof.

3. The method for preparing a hydrogel band-aid for bone repair according to claim 1, characterized in that: The molar ratio of polyethylene glycol succinimidyl succinate to alendronic acid is 1:1-5.

4. The method for preparing a hydrogel band-aid for bone repair according to claim 1, characterized in that: After the polyphenols are mixed with metal ions, metal ion-polyphenol complex nanoparticles are formed; Then, the metal ion-polyphenol complex nanoparticle dispersion and the alendronic acid-modified polyethylene glycol succinimidyl succinate solution are uniformly mixed, the solid and the liquid are separated, and the solid is dried to obtain a hydrogel; The molar ratio of metal ions, polyphenols and alendronic acid-modified polyethylene glycol succinimidyl succinate is 1.5-2.5:1:2-3.

5. The method for preparing a hydrogel band-aid for bone repair according to claim 1, characterized in that: The polyphenol is selected from one or a combination of tannic acid, gallic acid, epigallocatechin gallate, catechin or anthocyanin.

6. The method for preparing the hydrogel bandage for bone repair according to claim 5, characterized in that: The polyphenol is epigallocatechin gallate.

7. The method for preparing a hydrogel band-aid for bone repair according to claim 1, characterized in that: The metal ion is selected from one or a combination of calcium ion, zinc ion, magnesium ion or strontium ion.

8. The method for preparing the hydrogel band-aid for bone repair according to claim 7, characterized in that: The metal ions are calcium ions and / or zinc ions.

9. A hydrogel bandage for bone repair, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.

10. Use of the hydrogel bandage for bone repair according to claim 9 in treating osteoporotic bone defects.

Citation Information

Patent Citations

  • Preparation method of natural supramolecular hydrogel material capable of promoting osteogenic differentiation

    CN114796605A

  • Preparation method of collagen drug-loaded sponge for osteoporotic bone defect repair

    CN117899267A

  • Polymer-linked-biophosphonate inhalant formulations and methods for using the same

    US20080182823A1

  • Bone-targeted extracellular vesicle, and preparation method therefor and use thereof

    WO2023226203A1

Cited By

  • Targeted pathological B cell temperature-sensitive hydrogel bone repair material as well as preparation method and application thereof

    CN120346370A

  • A pathological b cell targeted thermosensitive hydrogel bone repair material and a preparation method and application thereof

    CN120346370B